2014
DOI: 10.1007/s13277-014-1792-5
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of base excision repair gene expression and enhanced proliferation in head and neck squamous cell carcinoma

Abstract: Defects in the DNA damage repair pathway contribute to cancer. The major pathway for oxidative DNA damage repair is base excision repair (BER). Although BER pathway genes (OGG1, APEX1 and XRCC1) have been investigated in a number of cancers, our knowledge on the prognostic significance of these genes and their role in head and neck squamous cell carcinoma is limited. Protein levels of OGG1, APEX1 and XRCC1 and a proliferation marker, Ki-67, were examined by immunohistochemical analysis, in a cohort of 50 HNSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 59 publications
4
31
0
Order By: Relevance
“…We observed a high immunoexpression of APE‐1 in 64.6% of OTSCC tumors. Similar results have been reported by Hsia et al in OSCCs, by Mahjabeen et al in tumors from head and neck region (HNSCC), and by Koukourakis et al in locally aggressive HNSCC, including ten cases of OSCC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed a high immunoexpression of APE‐1 in 64.6% of OTSCC tumors. Similar results have been reported by Hsia et al in OSCCs, by Mahjabeen et al in tumors from head and neck region (HNSCC), and by Koukourakis et al in locally aggressive HNSCC, including ten cases of OSCC.…”
Section: Discussionsupporting
confidence: 90%
“…The expression of proteins associated with DNA repair, including APE‐1 and XRCC‐1, has been demonstrated in several types of cancer, including carcinomas of cervix, ovary, prostate, gastro‐esophageal tract, pancreas, lung, bladder, and head and neck, as well as in osteosarcoma and pediatric ependymoma . The goal of this study was to investigate the immunoexpression of APE‐1 and XRCC‐1 and its association with clinical, histologic, and survival parameters in a cohort of OTSCC in order to investigate a possible prognostic value of these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first demonstration for an association of HPV infection in OPSCC with modulation of BER protein levels, albeit in only two cell lines, and is therefore a novel finding. However there are reports that in general that HNSCC patients can have upregulated protein expression of BER proteins including XRCC1 [25], APE1 [22] and PARP-1 [27]. Previously, it has been reported that the HPV E6 protein can bind XRCC1, interfere with BER efficiency and increase sensitivity to MMS [31].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, high XRCC1 protein expression in HNSCC patients correlates with poorer survival particularly to those that received chemoradiation [25]. Upregulation of APE1 protein expression has been observed in HNSCC tissues [22], and has been linked to resistance to chemoradiation and poorer survival [26]. Finally, poly(ADP-ribose) polymerase 1 (PARP-1) is overexpressed in nasopharyngeal carcinoma cells and tissues, and PARP inhibitors radiosensitise cells to IR whilst reducing tumour growth in combination with IR in xenograft models [27].…”
Section: Introductionmentioning
confidence: 99%
“…25,26 OGG1 mutants with abolished or decreased 8-OG repair activity have been found in many tumor specimens. 27,28 A common OGG1 polymorphism, S326C, which lowers BER activity, is positively associated with frequency of cancers of the digestive system and the lung. 29–31 In addition to its prominent association with genetic mutations leading to malignancies, OGG1-mediated repair of 8-OG has been associated with inflammation-related pathologies as well.…”
Section: Introductionmentioning
confidence: 99%